III-VI metal chalcogenide semiconductor nanosheets and heterostructures - Mudd, Garry William (2016)
This thesis presents an investigation into the properties of III-VI metal chalcogenide semiconductor nanosheets and demonstrates their capability to enhance graphene-based optoelectronics. Strong quantization effects and tunable near-infrared-to-visible (NIR-to-VIS) photoluminescence emission are reported in mechanically exfoliated crystals of gamma-rhombohedral semiconducting InSe at room temperature. The optical properties of InSe nanosheets differ qualitatively from those reported for transition metal dichalcogenides and indicate a crossover from a direct-to-indirect band gap semiconductor when the InSe nanosheet thickness, L, is reduced to a few nanometres, corresponding to the emergence of a ‘Mexican hat’ energy dispersion for the valence band. At low temperature, radiative recombination of photoexcited carriers bound at native donors and acceptors in nominally undoped InSe nanosheets is observed. A two-dimensional hydrogenic model for impurities is used to describe the increase in binding energy with decreasing L and reveals a strong sensitivity of the binding energy on the position of the impurities within the nanolayer. The application of a magnetic field, B, perpendicular to the plane of InSe nanosheets induces a marked change of the observed optical spectrum. A transfer of intensity from a low-to-high energy component at high B corresponds to an indirect-to-direct band gap crossover, which arises from the Landau quantisation of the in-plane carrier motion and crossover between hole cyclotron orbits centred on closed edges of the valence band. High broad-band (NIR-to-VIS) photoresponsivity is achieved in mechanically formed InSe–graphene van der Waals heterostructures, which exploit the broad-band transparency of graphene, the direct bandgap of InSe, and the favourable band line up of n-InSe with graphene. The photoresponse is dependent on the electron transit time through the InSe layer, as evaluated by a semiclassical model.